Biodiversity Profile of Charkishoreganj Munshiganj, Bangladesh - Chowdhury, G. W.; Ruma, F.; Sarker, N. B.; Yasmin, A.; Mobassera, W.; Jahan, I; Chowdhury, M.; Islam, Md. A. (Ecoprint: An International Journal of Ecology, 2016)
Available with fulltext. Key words: People's Biodiversity Register Ecoprint An International Journal of Ecology Vol. 14, 2007 Page: 73-77 Uploaded date: 31 May, 2011